Bridging the Gap Between Declarative and Procedural Knowledge in the Training of Translators: Meta-Reflection Under Scrutiny - Alves, Fábio (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractAiming at reassessing the declarative/procedural knowledge dichotomy in the training of translators, this article builds on connectionist principles (Elman et al. 1996) and Relevance Theory (Sperber & Wilson 1986/1995) to present the rationale for a project which, from a pro-active standpoint, suggests that translator’s training could incorporate some of the methodologies used for data elicitation in translation process studies and apply them in classroom settings as an avenue to increase the level of awareness among novice translators. Meta-reflection, according to the article, is the key to promote awareness-raising and, as a consequence, an increment in the quality of translator.s training.